Cardiac Arrhythmias From Basic Mechanism to State-of-the-Art Management - Kibos, Ambrose S.; Knight, Bradley P.; Essebag, Vidal; Fishberger, Steven B.; Slevin, Mark.; Țintoiu, Ion C.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2014)
The past 50 years have witnessed the growth and evolution of clinical electrophysiology from a field whose goals were simply to understand of the mechanisms of arrhythmia to one of significant therapeutic impact. The development and refinement of implantable devices and catheter ablation have made non-pharmacological therapy a treatment of choice for most arrhythmias encountered in clinical practice. Cardiac Arrhythmias: From Basic Mechanism To State-of-the-Art Management provides an electrophysiologic approach to arrhythmias predicated on the hypothesis that a better understanding of the mechanisms of arrhythmias will lead to more successful and rationally chosen therapy. It encompasses the anatomy of arrhythmias, diagnostic methods, comorbid diseases, and the treatment of all forms of cardiac arrhythmias. It discusses modern ablation and mapping techniques, while reviews the methodology required to define the mechanism and site of origin of arrhythmias, so that safe and effective therapy can be chosen. It will thus be of interest to all involved in the management of these patients, from clinical cardiac electrophysiologists themselves to clinical cardiologists, interventionalists, cardiac surgeons, emergency medicine physicians and researchers in basic cardiac science.
Section  I. Basics in arrhythmias anatomy -- Section II. Diagnostic methods -- Section III- Diseases associated with arrythmias -- Section IV-  Treatment.
Keywords: Cardiology; Cardiology